2007
DOI: 10.1177/1460458207079836
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accuracy of drug interaction alerts triggered by two electronic medical record systems in primary healthcare

Abstract: This article presents a study to evaluate the accuracy of drug interaction (DI) alerts triggered by two electronic medical record (EMR) systems in primary healthcare. A scenario-based software architecture analysis methodology (SAAM) was used with drug-drug interaction (DDI) pairs in hypothetical patient scenarios. A literature search identified common drugs used in the management of conditions in the elderly population. Three reference programs determined the level of severity of drug interactions, and a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…Our results support international literature in this area. Studies have shown variation and deficiencies in drug interaction decision support in pharmacy software systems in the United States, 22 in clinical software systems used in primary care in Canada, 23 and in drug interaction software for personal digital assistants 20 , 21 . A study of German GPs found that they wanted detailed drug interaction information, but their needs were not being met for some components (eg, management of interactions, outcomes) 24 …”
Section: Discussionmentioning
confidence: 99%
“…Our results support international literature in this area. Studies have shown variation and deficiencies in drug interaction decision support in pharmacy software systems in the United States, 22 in clinical software systems used in primary care in Canada, 23 and in drug interaction software for personal digital assistants 20 , 21 . A study of German GPs found that they wanted detailed drug interaction information, but their needs were not being met for some components (eg, management of interactions, outcomes) 24 …”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the misuse, disuse, and abuse of automation are important human factors and ergonomics topics (Parasuraman and Riley, 1997). Evidence about why CDS is ignored or overridden is similar to what has been found studying automation in other domains-the research on CDS has identified low specificity, low sensitivity, unclear information content, unnecessary workflow disruptions, and poor usability all as contributing factors (Miller et al, 2005;Saleem et al, 2005;Gaikwad et al, 2007). In fact, in a paper titled "Grand Challenges in Clinical Decision Support" (Sittig et al, 2008) 10 grand challenges for CDS were posed, and the #1 ranked challenge was improving the human-computer interface.…”
Section: Cds Human Factors and Ergonomics Issuesmentioning
confidence: 73%
“…15,16 At the very least, poor implementation of eCDS systems leads to wasted effort and money by failing to accomplish its goal. 17,18 At worst, it leads to unnecessary patient morbidity or mortality by serving as a time-consuming distraction to physicians. 19,20 …”
mentioning
confidence: 99%